CERAMICS IN RESTORATIVE AND PROSTHETIC DENTISTRY1 - Kelly, J. Robert (Annual Review of Materials Research, 1997)
▪ Abstract This review is intended to provide the ceramic engineer with information about the history and current use of ceramics in dentistry, contemporary research topics, and potential research agenda. Background material includes intra-oral design considerations, descriptions of ceramic dental components, and the origin, composition, and microstructure of current dental ceramics. Attention is paid to efforts involving net-shape processing, machining as a forming method, and the analysis of clinical failure. A rationale is presented for the further development of all-ceramic restorative systems. Current research topics receiving attention include microstructure/processing/property relationships, clinical failure mechanisms and in vitro testing, wear damage and wear testing, surface treatments, and microstructural modifications. The status of the field is critically reviewed with an eye toward future work. Significant improvements seem possible in the clinical use of ceramics based on engineering solutions derived from the study of clinically failed restorations, on the incorporation of higher levels of “biomimicry” in new systems, and on the synergistic developments in dental cements and adhesive dentin bonding.
Keywords: history